Le chronotope dans les récits de H. P. Lovecraft - Gadomska, Katarzyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
The present work is a study of the chronotope in the short stories of H.P. Lovecraft. Particular attention should be drawn to the dichotomy of time and space. Afterwards, the structures typical for the topology of the world presented in the fantastic production of H.P. Lovecraft are analyzed. At last, the characteristic distortions, space and time paradoxes are indicated in this paper.
Chronotope in the stories of H.P. Lovecraft